Lewis and Clark : a prairie dog for the president - Redmond, Shirley-Raye, 1955-; Manders, John (New York : Random House, 2003)
Introduces Meriwether Lewis and William Clark who, during their exploration of the West for Thomas Jefferson, captured a prairie dog and sent it to the President as a gift
Keywords: Lewis, Meriwether, -- 1774-1809 -- Juvenile literature; Clark, William, -- 1770-1838 -- Juvenile literature; Jefferson, Thomas, -- 1743-1826 -- Juvenile literature; Lewis, Meriwether, -- 1774-1809; Clark, William, -- 1770-1838; Jefferson, Thomas, -- 1743-1826; Prairie dogs -- West (U.S.) -- Anecdotes -- Juvenile literature; Prairie dogs; Explorers; West (U.S.) -- Description and travel -- Juvenile literature; West (U.S.) -- Discovery and exploration -- Juvenile literature; West (U.S.) -- Discovery and exploration